TOWARDS UNDERSTANDING FINANCIAL BEHAVIOR OF SMES: ROLE OF SOCIO-PSYCHOLOGICAL FACTORS OF OWNER-MANAGER - Rabia RASHEED; Maria ABDUL RAHMAN; Syed Abid UR RAHMAN (Studia Universitatis Babeş-Bolyai Negotia, 2016)
Purpose - Understanding SMEs’ use/adoption of financial services is prerequisite for policy makers and managers of financial institutions interested in their growth and development. The study seeks to explore influence of personal characteristics of owner-manager on firms’ financial behavior to use financial services.